2012
DOI: 10.1186/ar3835
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid counteracts B cell proliferation and plasmablast formation in patients with systemic lupus erythematosus

Abstract: IntroductionClinical trials revealed a high efficacy of mycophenolate mofetil (MMF) in inducing and maintaining remission in patients with class III-V-lupus nephritis. Also extrarenal manifestations respond to MMF treatment. However, few attempts have been undertaken to delineate its mechanism of action in systemic lupus erythematosus (SLE) a disease characterized by enhanced B cell activation.MethodsClinical and paraclinical parameters of 107 patients with SLE were recorded consecutively and analyzed retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 42 publications
6
58
3
Order By: Relevance
“…Mycophenolate mofetil selectively inhibits the growth of T and B cells and does not affect other immune cells because other cells are able to recover purines via a separate salvage pathway. 26 In addition, Eickenberg et al 27 investigated patients with systemic lupus erythematosus and reported that transitional and naive B-cell counts were significantly higher in patients who were taking MMF compared with those who were taking AZA, but markedly lower frequencies of plasmablasts were detected in patients who were mitoxantrone 16 efficacy studies, our MMF-treated patients had similar ARR after treatment and relapse-free rates but tended to have lower ARR and EDSS scores before treatment than in other immunosuppressant studies (Table 3). Our study comprised only 7 patients (12%) with severe neurological impairments (EDSS score >6), whereas the studies that used mitoxantrone 16 and rituximab 11 consisted of 26% to 45% of those cases.…”
Section: Discussionmentioning
confidence: 98%
“…Mycophenolate mofetil selectively inhibits the growth of T and B cells and does not affect other immune cells because other cells are able to recover purines via a separate salvage pathway. 26 In addition, Eickenberg et al 27 investigated patients with systemic lupus erythematosus and reported that transitional and naive B-cell counts were significantly higher in patients who were taking MMF compared with those who were taking AZA, but markedly lower frequencies of plasmablasts were detected in patients who were mitoxantrone 16 efficacy studies, our MMF-treated patients had similar ARR after treatment and relapse-free rates but tended to have lower ARR and EDSS scores before treatment than in other immunosuppressant studies (Table 3). Our study comprised only 7 patients (12%) with severe neurological impairments (EDSS score >6), whereas the studies that used mitoxantrone 16 and rituximab 11 consisted of 26% to 45% of those cases.…”
Section: Discussionmentioning
confidence: 98%
“…In SLE, MMF, but not AZT or hydroxychloroquine, treatment has been associated with reduced frequency of switched memory B cells and modest decreases in levels of serum Ig and of anti‐dsDNA antibodies 40, 41, 42. The composition of B cell subpopulations may vary between individuals with SLE and after rituximab; repopulation appears to recapitulate ontogeny, perhaps further influenced by antigen stimulation 43.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these properties, it is not surprising that significant hypogammaglobulinaemia associated with bronchiectasis has been reported in seven of 23 patients with recurrent chest infections postrenal transplantation [81]. MMF-induced hypogammaglobulinaemia has also been observed in patients with systemic lupus erythematosus though it is unclear whether this was accompanied by a significant burden of infections [82]. In contrast to MMF, azathioprine a related purine inhibitor has minimal propensity to induce hypogammaglobulinaemia [83].…”
Section: Mycophenolate Mofetilmentioning
confidence: 97%